Size and Spectroscopic Evolution of HectoMAP Quiescent Galaxies - Ivana Damjanov; Jubee Sohn; Margaret J. Geller; Yousuke Utsumi; Ian Dell’Antonio (The Astrophysical Journal, 2023)
The HectoMAP survey provides a complete, mass-limited sample of 30,231 quiescent galaxies with i -band Hyper Suprime-Cam Subaru Strategic Program (HSC SSP) imaging that spans the redshift range 0.2 < z < 0.6. We combine half-light radii based on HSC SSP imaging with redshifts and D _n 4000 to explore the size–mass relation, ${R}_{e}=A× M_{* }^{α }$ , and its evolution for the entire HectoMAP quiescent population and for two subsets of the data. Newcomers with 1.5 < D _n 4000 < 1.6 at each redshift show a steeper increase in A as the universe ages than the population that descends from galaxies that are already quiescent at the survey limit, z ∼ 0.6 (the resident population). In broad agreement with previous studies, evolution in the size–mass relation both for the entire HectoMAP sample and for the resident population (but not for the newcomers alone) is consistent with minor merger driven growth. For the resident population, the evolution in the size–mass relation is independent of the population age at z ∼ 0.6. The contrast between the sample of newcomers and the resident population provides insight into the role of commonly termed “progenitor bias” on the evolution of the size–mass relation.